Adenosine Diphosphate (ADP) Breakdown in Human Plasma with Reference to Platelet Aggregation and Uraemia - Gan, I. E. T; Firkin, B. G (Thrombosis and Haemostasis, 1968)
1. A correlation between platelet aggregation and the plasma enzyme(s) ability to degrade Adenosine Diphosphate (ADP) has been confirmed.2. This plasma activity has been shown to be reduced in 6 patients with uraemia in whom platelet aggregation was demonstrably impaired but not in two whose platelet function was normal. The incorporation of 14C labelled ADP-8-14C was also only reduced in uraemic patients with abnormal platelet aggregation.3. These findings are discussed with particular reference to possible implication in mechanism involved in ADP aggregation of platelets.